Spreading the Gospel of Good Health: Assessing Mass Women's Magazines as Communication Vehicles to Combat Health Disparities Among African Americans - Lumpkins, Crystal Y. (Journal of media and religion, 2012)
A burgeoning interest and curiosity in spirituality and religion among the general and minority populations in the United States has led many health communication scholars to consider the implications these factors have on communicating health risk. Mass magazines, a popular source of health information among women and minorities, are well positioned to reach these targeted audiences and assist health communicators achieve their communication objectives. However, results from this pilot study suggest these vehicles are largely untapped channels to disseminate this type of culturally targeted health information. Content analyses of consumer mass magazines reveal Essence, an ethnic magazine, does incorporate some spiritual and religious factors; however, general readership magazines do not. Given the current spiritual landscape, health communicators can utilize not only ethnic magazines but also other women's mass magazines as health promotion channels to communicate health risk among African American women.